"Aprovechamiento de los materiales residuales de las actividades mineras del Distrito San Gerardo cantón Camilo Ponce Enríquez provincia del Azuay" - Bravo Aillón, Jhoni Iván (2010)
The present investigation is part of one of the most disturbing effects important that man, as a geological agent, produces in the natural environment, in the accumulation of large volumes of solid waste from extractive mining activities, in order to take advantage of and reuse the residual materials product of the mining activities of the San Gerardo District Canton Camilo Ponce Enríquez Province of Azuay ”. To develop, the concession areas in; BEAUTIFUL GALA, PAPERCORP, COLD STREAM, PINGLIO, PARALLELS, RENAISSANCE M-3. Covering the river basin of the Rio Chico on a surface approximately 2,500 hectares. In chapter I consider unused materials or environmental passives known as: waste rock or dumps (product of excavations cruise ships needed to reach the mineralized bodies) to extract them. Final glues (treatment of minerals in pulp form with a solid fraction and an aqueous fraction containing different particles suspended minerals and / or dissolved ions). In Chapter II he determines several studies that have verified the contamination generated by mining. As well as the influence of unused waste in the mining activities of the San Gerardo district to prepare a proposal decontamination of the Rio Chico basin. Standards and provisions of the New Mining Law. And environmental management. The formulation of hypotheses speculates that the level of contamination of the water of the river basin reduces by taking advantage of unused waste In chapter III the scientific research methods used were: Observation Method, Inductive Method, Documentary Research Method bibliographic. The techniques used were the interview and survey techniques made to: Mining businessmen, workers, community, professionals in the branch .................................... ......................